Proprioceptive contact force and contact point estimation in a stationary snake robot - Løwer, Jostein; Gravdahl, Irja; Varagnolo, Damiano; Stavdahl, Øyvind (IFAC-PapersOnLine, 2022)
Measuring contact forces and knowing how and where a robot is interacting with obstacles in its environment is particularly useful for developing physics-based Obstacle-Aided Locomotion strategies for snake robots. The current paradigm for obtaining such measurements is mostly hardware-based, and is achieved through physical sensors that are attached to the outside of the chassis. Since external sensors are subject to wear and tear, it is in general preferrable to estimate external forces using solely sensors that may be hidden within the body of the robot. In this paper we contribute towards devising a method for performing such estimation tasks; more precisely, and building on the work of Liljebäsck et. al., we analyze the kinematics of the snake robot systems, and propose a method to estimate contact forces and contact points in a case where the robot remains stationary starting from proprioceptive measurements of constraint forces, accelerations, and force balance equations of a rigid body. The efficacy of the estimators in estimating contact point, contact force and direction is verified experimentally.